Analisa Mengenai Adanya Perlindungan Hukum Terhadap Tindak Kekerasan kepada Anak di Indonesia - Amanda, Regitia (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2022)
An individual basically when born has the right to a decent living and is well protected by the State so that he can grow and develop, and is protected from all forms of violence that occur by starting to educate and direct children from a young age by instilling important values in life. However, the occurrence of violence against children in Indonesia is very frequent and commonplace. The forms of violence also vary from time to time. Meanwhile, children are the generation of heirs and also belong to a nation that protects and realizes its ideals which can determine the future of a nation. Crime is an act against the law and the perpetrator is punished. Violence and other crimes are on the rise. Violence is any indiscriminate act carried out by a person with the intent to cause physical or mental harm. The first education of a child starts from the first environment in which the child lives, namely parents. Parents have a vital role in supporting and protecting, but in reality, violence against children often occurs as a result of parents. Meanwhile, the role of the parental environment in increasing children’s success factors and assisting children’s development is very important for children’s development, especially in shaping children’s character, enabling them to behave ethically, morally and ethically, as well as building children’s respect for others and being able to believe in themselves. In the future, it can help the child’s development in terms of the child’s feelings or reactions and the child’s future activities to underlie how the child behaves once he enters society. Therefore, we must find a way so that acts of violence against children do not occur regularly and the government takes firm action against perpetrators of violence.